2022
DOI: 10.1016/j.envres.2022.112758
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and COVID-19 incidence during four 2020–2021 case surges

Abstract: Background Air pollution exposure may make people more vulnerable to COVID-19 infection. However, previous studies in this area mostly focused on infection before May 2020 and long-term exposure. Objective To assess both long-term and short-term exposure to air pollution and COVID-19 incidence across four case surges from 03/1/2020 to 02/28/2021. Methods The cohort included 4.6 million members from a large integrated health care system in sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Ambient air pollution has been associated with SARS-CoV-2 incidence in the Netherlands ( Andree, 2020 ; Cole et al, 2020 ) and in several other countries among others Canada ( Stieb et al, 2020 ), USA ( Sidell et al, 2022 ), Italy ( De Angelis et al, 2021 ) and Germany ( Prinz and Richter, 2022 ), mostly in ecological settings. We therefore included ambient PM 10 and NO 2 concentrations as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient air pollution has been associated with SARS-CoV-2 incidence in the Netherlands ( Andree, 2020 ; Cole et al, 2020 ) and in several other countries among others Canada ( Stieb et al, 2020 ), USA ( Sidell et al, 2022 ), Italy ( De Angelis et al, 2021 ) and Germany ( Prinz and Richter, 2022 ), mostly in ecological settings. We therefore included ambient PM 10 and NO 2 concentrations as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…No association between PM 2.5 or NO 2 and mortality was found in a prospective longitudinal study conducted in Ontario, Canada, while significant associations were estimated with hospitalizations and accesses to intensive care units [9]. In contrast, positive associations between PM 2.5 exposure and COVID-19 incidence were estimated in northern Italy [10] and southern California [11].…”
mentioning
confidence: 90%
“…long model, and the confounders Hispanic, Mining or Agriculture, Public Transportation, Time to Work, Income Inequality, and Population Density were signi cant at different time periods of the model.DiscussionOur study analyzed the spatial correlation between COVID-19 mortality and long-term DPM concentration as a surrogate for exposure across the continental United States during three waves of the COVID-19 pandemic during 2020. Our results suggested that long-term exposure to DPM may have been an important factor in COVID-19 mortality during the rst two waves of the disease and that long-term DPM exposure may have been more highly in uential during the January-May wave Sidell et al (2022). examined associations between air pollution exposure and COVID-19 incidence for monthly and annual averages of PM 2.5 , nitrogen dioxide (NO 2 ), and ozone (O 3 ) over four waves corresponding to those in our study plus January-February, 2021 for a Southern California cohort.…”
mentioning
confidence: 69%